UJI KADAR ALKOHOL PADA TAPAI KETAN PUTIH DAN SINGKONG MELALUI FERMENTASI DENGAN DOSIS RAGI YANG BERBEDA - Zainal Berlian; Fitratul Aini; Resti ulandari (Biota, 2016)
Alcohol is widely used in industry, such as a solvent, as a synthesis in the chemical industry and at the present time alcohol is also used to fuel cars. This study aims to determine the differences in the level of alcohol contained in Tapai white sticky rice and cassava with different doses of yeast. This research was conducted in the laboratory of Chemical Biology Education Studies Program Faculty of Tarbiyah and Teaching UIN Raden Fatah Palembang in August 2015. The method used in this study is the experimental method using a completely randomized factorial design consisting of two factors, namely the type of fermentation ingredients: (Tapai white sticky rice and cassava) and a dose of yeast (0.5%, 1% and 1.5%) with four replications. Data were analyzed by ANOVA followed by two lines and test Beda Distance Real Duncan (BJND) at the level of 1%. Based on the results of the analysis showed that the alcohol content of the type of material the value of F count = 82.14> F table = 8.29 and yeast dose of F count = 812.14> F table = 6.01. From the results of this study concluded that: 1) There is a very real difference to the alcoholic content of fermented glutinous white Tapai and cassava. 2) There is a very real effect of different doses of yeast against alcohol content.